Research of Acoustic Emission Health Monitoring Test of Plane Welding Joint. Issue 2 (October 2020) - Zhang, Haibing; Wang, Yongqi; Zhu, Longxiang
Abstract: The welding joint is the key area of Aircraft bearing structure, which is not only subjected to alternating fatigue force, but also to the impact force during takeoff and landing. In this paper, the formation model of fatigue crack is studied, and the health monitoring of aircraft welds based on optical fiber acoustic emission technology is proposed in combination with the principle of acoustic emission detection. The sensor arrangement scheme and test conclusion are given through the actual acoustic emission test of simulated damage of welding joint, which provides the basis for the health monitoring of welding joint of aircraft in service.